Atmospheric chemistry of CF3(CX2)2CH2OH: rate coefficients and temperature dependence of reactions with chlorine atoms and the subsequent pathways of alkyl and alkoxy radicals (X = H, F). Issue 68 (5th July 2016) - Bai, Feng-Yang; Liu, You-Jun; Wang, Xu; Sun, Yan-Qiu; Pan, Xiu-Mei
Abstract : The atmospheric and kinetic properties of CF3 (CX2 )2 CH2 OH (X = H, F) with chlorine atoms were studied by density functional and canonical variational transition state theories in conjunction with the small-curvature tunneling correction. Abstract : The atmospheric and kinetic properties of CF3 (CX2 )2 CH2 OH (X = H, F) with chlorine atoms were studied by density functional and canonical variational transition state theories in conjunction with the small-curvature tunneling correction. The minimum energy path was obtained by the CCSD(T)/6-311++G(d, p)//B3LYP/6-311G(d, p) method. The H-abstraction channel from the –CH2 O– group was found to be the dominant channel, whereas that from the –OH site of the title reactions may be negligible because of the high barrier. All rate constants computed within 200–1000 K are in reasonable agreement with the available experimental values. The degradation mechanism of CF3 (CX2 )2 CH2 OH is discussed. The subsequent pathways of the CF3 (CX2 )2 C˙HOH and CF3 (CX2 )2 C(O˙)HOH radicals were studied. The atmospheric lifetime and global warming potentials (GWPs) of CF3 (CX2 )2 CH2 OH were computed, and it is shown that fluorine substitution may increase the lifetime and GWPs. It is also indicated that fluorine substitution may decrease the reactivity. The reaction enthalpies and reaction Gibbs free energies for all relevant reactions were discussed. The rate coefficient expressions for the title reactions obtained are k T 1 = 5.75 × 10 −17 T 2.26 exp(428.02/ T ) and k T 2 = 1.30 × 10 −17 T 1.96 exp(67.40/ T ) per cm 3 per molecule per s.